Floating drift on a vibrofluidized relaxing granular slope - Yuki Yamamoto; Hiroaki Katsuragi (Physical Review Research, 2024)
For floating on water, low density is the sole necessary factor. However, it has not been clarified how to floatingly drift on fluidized granular matter. Although this problem relates to various natural phenomena such as debris flow and lunar boulder-fall traces, fundamental aspects of the floating drift on granular flow have not been revealed. Therefore, the motion of a sphere on a vibrated granular slope is experimentally investigated in this study. As a result, we find that the sinking depth of the floating sphere can be explained by a modified buoyancy model. In addition, the downstream velocity of the drifting sphere can be understood by a force balance between flow-induced pushing force and frictional resistance force. This force balance results in a nonsteady but stable floating drift on the relaxing granular slope.